The role of neem leaves as organic pesticides in chili pepper (Capsicum frutescens) - SOPIALENA SOPIALENA; SURYA SILA; ROSFIANSYAH ROSFIANSYAH; JULI NURDIANA (Smujo International, 2018)
Sopialena, Sila S, Rosfiansyah, Nurdiana J. 2018. The role of neem leaves as organic pesticides in chili pepper (Capsicum frutescens). Nusantara Bioscience 10: 246-250. The agricultural crops and horticultural plants are always under constant assault caused by diseases, insect pests, viruses, and other pathogens which may substantially reduce yield. Chili Pepper (Capsicum annum L.) is a popular horticultural plant of the Solanaceae family in Indonesia. Some serious diseases widely found in chili peppers, are anthracnose (Colletotrichum capsici), leaf spot (Cercospora capsici) and fruit rot (Phytophthora capsici). To manage the potential problems, this study is aimed to provide an explanatory knowledge of the use of plant-based pesticide to control the diseases in chili peppers. The information is meant to fill the knowledge gaps in the use of plant-based pesticide to control the chili diseases. The use of nonchemical pesticide benefits not only the environment but also as an organic strategy for disease management. This research used a randomized complete block design (RCBD) categorized into four groups and six different treatments. The organic pesticides were prepared from the extract of neem leaves, soursop leaves, lemongrass extract, tuba root extract, and kenikir/Cosmos caudatus extract). The result indicates that neem leaves are the most effective organic pesticides to control the chili pepper disease in Indonesia.